Transcatheter Tricuspid Valve Replacement: Current Options and Future Perspectives - Guido Del Monaco; Gianluca Mincione; Alessandro Sticchi; Bernhard Reimers; Antonio Colombo; Antonio Mangieri (Reviews in Cardiovascular Medicine)
Tricuspid regurgitation (TR) is a potentially lethal condition and represents a significant clinical challenge both for clinical and interventional cardiologists. Traditionally managed medically and surgically, transcatheter therapies are now an emerging option, especially in patients with prohibitive surgical risk due to age or comorbidities. Transcatheter tricuspid valve replacement (TTVR) is emerging as a potential solution for patients suffering from TR with positive clinical data supporting its use in a wide range of anatomies and clinical settings. However, the adoption of TTVR introduces new challenges, including a scarcity of long-term clinical risks of valve thrombosis, questions regarding the durability of implanted valves, and the potential higher risk for post-procedural pacemaker (PM) implantation.